2023
DOI: 10.48017/dj.v8i3.2669
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Code Switching Manifested by Filipino High School Teachers

Louie Villanueva,
Gamiao Bert

Abstract: The Philippines as an archipelago is a multilingual community, thus, analyzing discourses are advantageous to its scholars. Hence, the researchers extracted the respondents’ discourses in their online classes and investigated the types and patterns of code switching occurences among 9 teachers through qualitative and quantitative analyses. They adapted the typology by Poplack (1980) and Myers-Scotton (1989). Poplack classified code switching into tag, intersentential, and intrasentential but later, Myers-Scott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Although Lin and Lei's (2021) study showed relevance to bilingual instruction, it did too on the results of their study which showed that participants were happy with the English as Medium of Instruction (EMI) strategy, which enhanced their linguistic proficiency and disciplinary learning, which supports the findings of this study. Furthermore, the findings of this research reflect in the study of Villanueva and A Bert (2023), who firmly believed that the definition of an instructional medium needs to be operationally redefined. It should be inclusive in the sense that it does not isolate the classroom from the society in which it is situated.…”
Section: Table 4 Mean Difference (Control Group)supporting
confidence: 61%
“…Although Lin and Lei's (2021) study showed relevance to bilingual instruction, it did too on the results of their study which showed that participants were happy with the English as Medium of Instruction (EMI) strategy, which enhanced their linguistic proficiency and disciplinary learning, which supports the findings of this study. Furthermore, the findings of this research reflect in the study of Villanueva and A Bert (2023), who firmly believed that the definition of an instructional medium needs to be operationally redefined. It should be inclusive in the sense that it does not isolate the classroom from the society in which it is situated.…”
Section: Table 4 Mean Difference (Control Group)supporting
confidence: 61%